STUDI TENTANG FAKTOR – FAKTOR YANG MEMPENGARUHI KEPERCAYAANMASYARAKAT TERHADAP PARTAI POLITIK DI KECAMATAN DUMAI TIMUR KOTA DUMAI - Indah Wulan Sari; Sri Erlinda; Zahirman Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract:This research is based on influencing factors of public confidence to political party in comunity. The phenomenon that occurred in the area of East Dumai Subdistrict, the lack of public awareness to participate in the election of political parties in the community either teenagers or parents. The formulation of the problem in this research is What are The Factors That Affect Public Belief In Political Parties. The purpose of this study is to be known What are the Factors Affecting Public Beliefs Against Political Parties. The population of this research is Dumai Timur Dumai Town of 61,685 people. and the sample is 100 people. The sampling technique used is sampling and quota sampling. The instruments of data collection are observation, questionnaire, interview and documentation. This research is using Qualitative Descriptive analysis. The results of this study shows that the factors are influencing public confidence in political party in Dumai Timur of Dumai Town. Explained by the percentage of 100 respondents stated answer "Yes" 44,8% and answer "No" 55,2% hence can be seen factors which influences public confidence in political parties, there are seven (7) factors that influence public confidence in political parties such as: Political Socialization, Party Behavior, Party Intuition, Personal, Symbolic, Party Image, Motivation. With the highest percentage of answers as much as 75% of Personal Factors, Symbolic Factors and Party Image Factors that are believed to affect the communities confidence on political parties in Dumai Timur Dumai City.Keyword : Public Trust, Political Parties.